The risk of acute myocardial infarction development in long-term radiation exposure - A. B. Karpov; R. M. Takhauov; Yu. V. Semyonova; T. M. Litvinenko; D. Ye. Kalinkin; М. А. Varlakov (Бюллетень сибирской медицины, 2012)
Study of risk acute myocardial infarction (AMI) development in persons (80,2% males) exposed to long-term low doses ionizing radiation and chemical factors.Prospective cohort study of AMI morbidity in period 1998—2006 among the personal, exposed to long-term professional radiation and chemical factors.Risk AMI development increase in group of male personel exposed combined radiation and chemical factors. The obtained results indicate that possible summation of «traditional» AMI development risk factors and radiation factor negative influence on endothelial tissue.